Mitigating atmospheric methane emissions from Asian rice fields: a review of potential and promising technical options - I Gusti Ayu Agung Pradnya Paramitha (LIMNOTEK Perairan Darat Tropis di Indonesia, 2023)
Agriculture serves as a significant anthropogenic source of methane emissions. Numerous recent studies have examined the factors influencing methane emissions and have developed emission models. However, there is no a bridging review study related to methene emissions in Asia as one of the primary methane emitters. This review is divided into two manuscripts. In this first manuscript, I explore the process of methane emission and the factors that impact methane production and emissions. Meanwhile, the present state of studies conducted in various Asian countries and knowledge gaps are elaborated in the second manuscript. I elaborate several factors that influence methane production and their roles in the emission process. Further, I highlight that the gas is mostly produced in zero oxygen condition, although, a little concentration of methane also can be generated in oxic condition. This finding provides basic knowledge that contribute to the future research on methane emissions in rice field ecosystems.  Eventually, I also explore various recommended technical solutions to reduce the gas emission.